Qur'anic Interpretation of Hoax News: A Sociohistorical Approach and Its Relevance in the Digital Era - Siti Nur Kholifah (Lembaga Yasin AlSys, 2025)
The proliferation of hoaxes in the digital era has led to widespread social disruption, including within Muslim communities. This study investigates how the Qur’an addresses the issue of spreading false information through a sociohistorical interpretive approach, aiming to explore its relevance to contemporary digital challenges. The research is guided by two central questions: how does the Qur’an contextualize hoaxes within its historical setting, and how can its messages be actualized in today’s information landscape? Employing a qualitative methodology, the study utilizes a literature review and thematic analysis of selected verses—Al-Hujurat [49]:6, An-Nur [24]:11–16, and Al-Baqarah [2]:10—interpreted through asbab al-nuzul (circumstances of revelation) and social hermeneutics. The findings reveal that the Qur’an emphasizes core communicative values such as honesty, tabayyun (verification), and social responsibility. These principles are highly relevant in shaping ethical responses to misinformation in the post-truth era, particularly in addressing religion-based hoaxes. The study concludes by recommending the integration of Qur’anic interpretive principles into Islamic digital literacy curricula and the development of information governance frameworks rooted in ethical and civilizational values.